Cracking Control in Mezzanine Floor Slabs using Rice Husk Ash and Polypropylene Fibers - Cano, B. (2020)
The continuous population increase in recent years requires a greater number of households to be built quickly, with good materials and produced under quality standards that guarantee their manufacturing process. The prefabricated concrete, produced and supplied by concrete plants, is poured into the different structural elements, the mezzanine slabs being the most careful surfaces in the appearance of fissures; because being horizontal and having larger dimensions, the dimensional changes in the concrete appear more frequently due to the rapid loss of water from the surface of the concrete before setting; which generates superior stresses to the resistant capacity of the concrete at early ages, which affect the durability and reduce the resistance of the structures, causing greater economic expenses in maintenance and repairs. In the present investigation, 5%, 10% and 15% of rice husk ash was used as a replacement for cement and 900g/m3 of polypropylene fiber; The results indicate that as the percentage of rice husk ash increases, there is a reduction in the slump and the crack fissures, and that the resistance to compression and flexion decreases, with respect to the concrete pattern.